STEPS IN DIAGNOSIS OF CHRONIC IDIOPATHIC NEUTROPENIA: IS IT THE TIME FOR SERBIAN PATIENT REGISTRY? Chronic idiopatic neutropenia - steps in diagnosis - Veličković, Sanja; Vučić, Miodrag; Stefanović, Nikola; Veličković, Filip; Mauroudi, Eirini; Papadaki, Helen; Catić-Đorđević, Aleksandra Krsto (Acta medicae Medianae, 2022)
Chronic neutropenia corresponds with absolute count of neutrophils below 1.8 × 109 /L in last three months. Besides, neutropenia that persists more than three months and in absence of underlying diseases, chemical components, irradiation, use of particular drugs, inflammation, is defined as chronic idiopathic neutropenia (CIN). There are three types of CIN - severe, moderate and mild, with or without extrahaematopoietic manifestations. The aim of this report was to define a stratified approach toward patient with hypothesis of CIN, including timely patient recognition with consequent follow-up and actions afterwards based on recommendation from EuNet INNOCHRON- European Network for Innovative Diagnosis and Treatment of Chronic Neutropenias. Case presented 40-year-old female who went in Hematology Department at University Clinical Center Nis for regular health condition and blood count control. Since she was 21, she has been following neutropenia, which occurred immediately after first childbirth. Laboratory parameters and peripheral blood smear was into physiological range. Performed immune assays excluded the immune background of neutropenia. In the next step, we excluded viral infections as a cause of neutropenia with particular serological tests. Also, a bone marrow puncture was performed with physiological results. Chronic neutropenia can be associated with serious health complications. Similar to other European country we suggest to introduce defined approach of diagnose, registration and monitoring chronic neutropenia patients in Serbia throw Register.
Keywords: chronic idiopathic neutropenia, diagnostic approach, register